A safe and effective dose of cisplatin in hepatic arterial infusion chemotherapy for hepatocellular carcinoma. (3rd January 2013) - Osaki, Akihiko; Suda, Takeshi; Kamimura, Kenya; Tsuchiya, Atsunori; Tamura, Yasushi; Takamura, Masaaki; Igarashi, Masato; Kawai, Hirokazu; Yamagiwa, Satoshi; Aoyagi, Yutaka
Abstract Cisplatin (CDDP) is an anticancer agent that is commonly used in hepatic arterial infusion (HAI) chemotherapy for hepatocellular carcinoma (HCC). This study aimed to clarify the safe and effective dose of CDDP in HAI for HCC. The hypervascular area was measured in 42 HCCs before and after HAI with CDDP. Serum platinum concentration was quantified in the peripheral and/or middle hepatic veins by atomic absorption spectrometry. The relation between the HCC response and CDDP dose was statistically analyzed. The multiple HCC nodules in an individual case generally demonstrated the same response to CDDP. The free‐platinum concentration stayed relatively constant in the hepatic vein during HAI followed by a rapid decline, while total‐platinum gradually increased then slowly disappeared over several days. After CDDP‐HAI, 15 HCCs shrunk and 27 HCCs grew. The reduction rate in the shrunken nodules was tended to be correlated with CDDP dose after standardization with the target liver volume. On the other hand, the growth rate of the enlarged HCCs was significantly correlated with CDDP dose after normalization with creatinine clearance. These data support a recommendation of CDDP‐HAI infusion where the amount of CDDP (mg) administered is less than patient creatinine clearance (mL/min/1.73 m2) upon an assumption of HCC doubling time of 90 days, and the targeted liver is smaller than 200 times the CDDP dose (mg). A further analysis is required to define appropriate injection speeds.